2009
DOI: 10.1080/11250000802616817
|View full text |Cite
|
Sign up to set email alerts
|

New data on the taxonomy and distribution of Rodentia (Mammalia) from the western and coastal regions of Guinea West Africa

Abstract: We compiled the first taxonomic inventory of rodents inhabiting the region from northwestern Guinea to coastal Guinea and this enabled an improved understanding of the rodent fauna of this unexplored region at the western margin of the guineo-congolese forest block. Through standard cytogenetic and morphological analyses we described the presence of two sibling species of the genus Mastomys in West Africa. We report here the first records for Guinea of Arvicanthis ansorgei and M. mattheyi. Our data indicated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…() and Denys et al. () showed it to be present in villages of the prefecture of Kindia (west of Guinea). Recent city surveys in northern Nigeria (Kano, M. Garba, unpublished data) and eastern Gabon (Franceville, J. Mangombi, unpublished data) have also yielded house mouse specimens in areas where the species was not mentioned by Happold ().…”
Section: Introductionmentioning
confidence: 96%
“…() and Denys et al. () showed it to be present in villages of the prefecture of Kindia (west of Guinea). Recent city surveys in northern Nigeria (Kano, M. Garba, unpublished data) and eastern Gabon (Franceville, J. Mangombi, unpublished data) have also yielded house mouse specimens in areas where the species was not mentioned by Happold ().…”
Section: Introductionmentioning
confidence: 96%
“…nor any site in southern Mali contained a suite of species typical of the humid forests and associated savannas of the true Guinean zone, as that found in the countries bordering the Gulf of Guinea, from Guinea to Nigeria. These include Dendromus melanotis, Dephomys defua, Grammomys buntingi and G. macmillani, Hylomyscus alleni, H. baeri and H. stella, Hybomys trivirgatus, Lophuromys sikapusi, Malacomys edwardsi and M. cansdalei, Mylomys dybowskii, Oenomys ornatus, Praomys tullbergi, and Stochomys longicaudatus (Happold 1977;Gautun et al 1986;Decher 1997;Decher and Bahian 1999;Denys et al 2009). Most of them belong to a group of "West African endemics" (Musser and Carleton 2005), only a few of which (especially G. buntingi and L. sikapusi) reach the latitudes of our study sites, but mainly in coastal and northern Guinea up to southwestern Senegal (Casamance; Denys et al 2009;Granjon and Duplantier 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These include Dendromus melanotis, Dephomys defua, Grammomys buntingi and G. macmillani, Hylomyscus alleni, H. baeri and H. stella, Hybomys trivirgatus, Lophuromys sikapusi, Malacomys edwardsi and M. cansdalei, Mylomys dybowskii, Oenomys ornatus, Praomys tullbergi, and Stochomys longicaudatus (Happold 1977;Gautun et al 1986;Decher 1997;Decher and Bahian 1999;Denys et al 2009). Most of them belong to a group of "West African endemics" (Musser and Carleton 2005), only a few of which (especially G. buntingi and L. sikapusi) reach the latitudes of our study sites, but mainly in coastal and northern Guinea up to southwestern Senegal (Casamance; Denys et al 2009;Granjon and Duplantier 2009). Their absence in our samples confirms White (1983) and Dowsett-Lemaire and Dowsett (2005) who suggested that lowland forests in southern Mali should not be considered as typical GuineoCongolian rainforest based on the species composition of plants and birds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biodiversity has been our topic since the very beginning of our history (by the way, besides the last five years, the back issues of the Journal are freely available on our web page, http:// www.informaworld.com/ijz, starting from 1930: check them over), when the word had not yet been coined. The recent contributions of the Italian Journal of Zoology to the basic study of biodiversity reside in taxonomic revisions, descriptions of new species and higher taxa, phylogenetic analyses (see for instance the recent papers by Andreone et al 2009;Dell'Angelo et al 2009;Denys et al 2009;Stocchino et al 2009). Some of these studies are carried out on representatives of the Italian fauna, others are based on more or less "exotic" corners of the world.…”
mentioning
confidence: 99%